Estudos éticos em representação do conhecimento: uma análise da questão feminina em linguagens documentais brasileiras - Milani, Suellen Oliveira [UNESP] (2010)
Knowlede representation, as a process, as well as the tools that take part in it and the products that emanate from it are not, by any means, neutral, being soaked in moral values. In such landscape, problems of bias in representation may rise, such as gender issues, dicotomical categorizations and lack of warrant/ cultural hospitality. Concerning the women’s issue, supported only by a few initial reflexions by Berman (1993), Olson (1998, 2002), Caro Castro and San Segundo Manuel (1999), Morán Suárez and Rodríguez Bravo (2001), López-Huertas and Barité Roqueta (2002), López- Huertas, Torres and Barité (2004), López-Huertas Pérez and Torres Ramírez (2005), López-Huertas (2006, 2008a), Guimarães (2006b, 2007) and Rodríguez Bravo (2006, 2007), there is severe lack of literature related to representation and to the outlining of its epistemological frame, becoming necessary to verify how far the terms connected to the feminine issue are eventually inserted under bias in the tools of area. For such action, it was proposed to verify the presence of the following terms: female; femininity; feminism; feminist; maternal; motherly; woman(en), within the Brazilian indexing languages: Vocabulário Controlado Básico, Vocabulário Controlado USP (University of São Paulo), Terminologia de Assuntos da Fundação Biblioteca Nacional e Classificação Decimal de Direito. Each term identified in the alphabetic indexing languages had its descriptor and nondescriptors recorded, as well as the scope and remissive notes, related terms and hierarchic relations, whereas the incidences related to hierarchic indexing languages were systematized in compliance with the guidelines proposed by Olson (1998). Presented as results signs of biasses, as well as possible aid to attenuate them, as gateways to further discussions. Thus, discussions should continue being realized... (Complete abstract click electronic access below)